Case report: Ruptured internal carotid artery fusiform aneurysm mimicking pituitary apoplexy after stereotactic radiosurgery - Wang, Peng Wei; Chung, Ming Hsuan; Feng, Shao Wei; Liao, Hsiang Chih; Wu, Yi Chieh; Hueng, Dueng Yuan; Yang, Yun Ju; Ju, Da Tong (Frontiers in Neurology, 2023)
Pituitary adenomas are benign tumors of the anterior pituitary gland for which surgery or pharmacological treatment is the primary treatment. When initial treatment fails, radiation therapy should be considered. There are several case reports demonstrating radiation-induced vascular injury. We report an adult patient who presented with headache and diplopia for 6 months and a sellar tumor with optic chiasm compression. The patient received transnasal surgery, and the tumor was partially removed, which demonstrated adenoma. Stereotactic radiosurgery (SRS) was arranged. However, owing to progressive tumor growth, the patient received further transnasal surgery and stereotactic radiosurgery (SRS). After 14 years, the patient reported the sudden onset of headache and diplopia, and a ruptured fusiform aneurysm from the left internal carotid artery with pituitary apoplexy was diagnosed. The patient received transarterial embolization of the aneurysm. There were no complications after embolization, and this patient was ambulatory on discharge with blindness in the left eye and cranial nerve palsies. Aneurysm formation may be a complication of SRS, and it may occur after several years. Further research is needed to investigate the pathogenesis of radiosurgery and the development of cerebral aneurysms.